COVID-19 vaccine uptake, effectiveness, and waning in 82, 959 health care workers: A national prospective cohort study in Wales. Issue 8 (16th February 2022) - Bedston, Stuart; Akbari, Ashley; Jarvis, Christopher I.; Lowthian, Emily; Torabi, Fatemeh; North, Laura; Lyons, Jane; Perry, Malorie; Griffiths, Lucy J.; Owen, Rhiannon K.; Beggs, Jillian; Chuter, Antony; et al.
Highlights: 90% vaccine uptake by 30 Sept 2021, but uptake in more deprived areas was lower. BNT162b2 was 85% effective after 2 weeks from second dose and 52% from 22 weeks. Equitable effectiveness of BNT162b2 after second dose. Abstract: Background: While population estimates suggest high vaccine effectiveness against SARS-CoV-2 infection, the protection for health care workers, who are at higher risk of SARS-CoV-2 exposure, is less understood. Methods: We conducted a national cohort study of health care workers in Wales (UK) from 7 December 2020 to 30 September 2021. We examined uptake of any COVID-19 vaccine, and the effectiveness of BNT162b2 mRNA (Pfizer-BioNTech) against polymerase chain reaction (PCR) confirmed SARS-CoV-2 infection. We used linked and routinely collected national-scale data within the SAIL Databank. Data were available on 82, 959 health care workers in Wales, with exposure extending to 26 weeks after second doses. Results: Overall vaccine uptake was high (90%), with most health care workers receiving the BNT162b2 vaccine (79%). Vaccine uptake differed by age, staff role, socioeconomic status; those aged 50–59 and 60+ years old were 1.6 times more likely to get vaccinated than those aged 16–29. Medical and dental staff, and Allied Health Practitioners were 1.5 and 1.1 times more likely to get vaccinated, compared to nursing and midwifery staff. The effectiveness of the BNT162b2 vaccine was found to be strong and consistent across the characteristics considered; 52% three to six weeks after first dose, 86% from two weeks after second dose, though this declined to 53% from 22 weeks after the second dose. Conclusions: With some variation in rate of uptake, those who were vaccinated had a reduced risk of PCR-confirmed SARS-CoV-2 infection, compared to those unvaccinated. Second dose has provided stronger protection for longer than first dose but our study is consistent with waning from seven weeks onwards.